A method for testing spatial body distribution of concrete crack healing products

CN121297709BActive Publication Date: 2026-10-16SHANDONG UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511275918.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2026-10-16
Estimated Expiration
2045-09-08

AI Technical Summary

Technical Problem

[0003]二维平面光学显微镜观察裂缝横截面愈合产物填充率,该方法仅能观察表面裂缝的愈合状态,愈合产物的填充率,无法反应裂缝不同深度处愈合产物的沉积量和沉积状态

Benefits of technology

(1)本发明通过预制拼接裂缝、激光扫描获取三维点云数据,并利用MATLAB对裂缝两侧愈合产物表面进行对正拼接,实现了愈合产物空间体态的精准重构,突破了传统方法无法表征不同深度裂缝愈合情况的局限。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present application relates to a kind of concrete crack healing product spatial body state distribution test method, belong to concrete repair technical field.The method steps are as follows: (1) prefabricated concrete crack, utilize 2 concrete pieces splicing, form concrete crack;(2) concrete crack healing, design healing component and healing environment, then carry out crack healing;(3) concrete crack healing spatial body state distribution test, 2 concrete pieces are separated, crack healing product is attached on 2 concrete pieces, and crack healing product is reconstructed in space body state;(4) concrete crack healing potential evaluation, according to the reconstructed crack healing spatial body state, obtain crack filling rate, effective healing width of crack, sealing effect after crack healing.The present application realizes the accurate reconstruction of healing product spatial body state, and breaks through the limitation that traditional method cannot characterize the crack healing condition of different depths.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for testing the spatial morphological distribution of concrete crack healing products, belonging to the field of concrete repair technology. Background Technology

[0002] Concrete is a major construction material for important infrastructure in my country, used extensively in projects such as reservoir dams, undersea tunnels, and airport runways. Concrete boasts advantages such as high compressive strength, high overall strength, and low cost. However, its low tensile strength makes it prone to cracking under tensile stress. These cracks become channels for harmful media intrusion, accelerating the degradation of concrete's mechanical and durability properties. Imparting crack-healing capabilities to concrete can effectively cut off these channels and extend its service life. Concrete cracks are typically long and narrow with random orientations. Evaluation of concrete crack healing involves observing the cross-sectional filling rate of the healed product and the overall filling rate of the crack using a two-dimensional planar optical microscope, and reconstructing the healed concrete using computerized X-ray tomography.

[0003] Two-dimensional planar optical microscopy is used to observe the filling rate of healing products in the cross-section of cracks. However, this method can only observe the healing state and filling rate of the surface cracks, and cannot reflect the deposition amount and state of healing products at different depths of the crack. The overall filling rate of crack products can evaluate the overall amount and filling rate of healing products at the crack, but it is difficult to reflect the distribution state of the products at the crack. Computed tomography (CT) can reconstruct the concrete after crack healing and divide it into three parts based on the grayscale of hydrated cement, unhydrated cement, and void phases. Since the healing products at the crack are cement healing products and concrete matrix hydration products, both including hydrated calcium silicate gel and calcium hydroxide, they have the same grayscale, making it difficult to distinguish the healing products at the concrete matrix and the crack. In addition, CT reconstruction of the concrete after crack healing is time-consuming and costly, thus making it difficult to effectively characterize the spatial distribution of the healing products at the crack. Therefore, this invention is proposed. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for testing the spatial morphological distribution of concrete crack healing products.

[0005] The technical solution of the present invention is as follows: A method for testing the spatial volumetric distribution of concrete crack healing products, comprising the following steps: (1) Precast concrete cracks are formed by splicing two concrete pieces together. (2) Concrete crack healing: design the healing components and the healing environment, and then carry out crack healing; (3) Test on the spatial distribution of healing at concrete cracks: Two concrete slices were separated, and the healing products at the cracks were attached to the two concrete slices. The spatial distribution of the healing products at the cracks was reconstructed. (4) Evaluation of the healing potential of concrete cracks: Based on the healing space morphology at the reconstructed crack, the crack filling rate, the effective healing width of the crack, and the sealing effect after crack healing are obtained.

[0006] According to a preferred embodiment of the present invention, step (1) specifically includes the following steps: Prepare concrete cubes, cut the concrete cubes into slices with a thickness of 15mm-35mm, and polish the concrete slices. The exposed surface is used as the polishing surface. Use 600-grit, 800-grit, 1200-grit, or 1500-grit diamond or silicon carbide sandpaper for polishing. Use anhydrous ethanol or isopropanol as the polishing lubricant. The resulting surface has a height difference of 100nm-20μm. Two concrete slabs are joined together using a clamping and fixing device, with the polished surfaces facing each other and a joint reserved. The joint is a precast crack in the concrete, which can be a parallel crack or a V-shaped crack.

[0007] According to a further preferred embodiment of the present invention, the spacing between parallel cracks is 100-800 μm, and the opening angle of the V-shaped cracks is 3°-10°.

[0008] According to a preferred embodiment of the present invention, in step (2), the healing component includes an external healing agent and unhydrated cement at the crack. Based on the healing principle of the volcanic ash effect of the healing agent, matrix expansion and continuous hydration of unhydrated cement in the crack area, effective healing of cracks of different shapes (parallel cracks and V-shaped cracks) and different widths (100-800μm) can be achieved. The external healing agent is prepared in the form of a healing capsule. The structure of the external healing agent from the inside out is as follows: healing core, waterproof layer, and interlocking layer. The healing core includes the following components in parts by weight: 6-12 parts calcium sulfoaluminate expansion agent, 1-5 parts silica fume, 3-8 parts fly ash, 2-4 parts rice husk ash, and 2-6 parts bottom ash from waste incineration. Calcium sulfoaluminate expansion agent, silica fume, fly ash, rice husk ash and waste incineration bottom ash are placed in a granulator for granulation. The surface is sprayed with water or the powder is bound with sodium silicate solution. The resulting granules are placed in an oven at a temperature below 60°C to dry, thus obtaining the healing core. The outer surface of the healing core is coated with polyvinyl alcohol solution or epoxy resin to form a waterproof layer (to prevent the internal material of the core from hydrating prematurely and to provide sufficient chemical substances for subsequent crack healing). After sealing, the outer surface is in contact with standard sand, and the sand particles are left on the outer surface of the healing core. The outer surface of the healing core is rough and uneven, forming an interlocking layer, and an external healing agent is obtained. The external healing agent has the characteristics of high solid waste content, particle size not exceeding 8mm, and has the effect of healing cracks. By making full use of the unhydrated cement in the cracks and adding super-absorbent polymers to the concrete, we can achieve efficient healing of different crack shapes and widths, and combine external replenishment and internal generation of healing products. The superabsorbent polymer is sodium polyacrylate or polyacrylic acid-acrylamide copolymer, with a balanced swelling rate not exceeding 289 g / g.

[0009] According to a further preferred embodiment of the present invention, the dosage of the healing capsule is 5%-50% of the aggregate volume in the concrete, and the dosage of the superabsorbent polymer is 0.5%-5% of the cement mass in the concrete, with the two dosage ratio maintained at 10:1 to ensure efficient synergy between the two.

[0010] According to a preferred embodiment of the present invention, in step (2), the healing environment is a 97% relative humidity environment (20±2℃, 97%RH) and a wet-dry cycle in water for 28 days (20±2℃, 1h in water, 23h in air) to achieve concrete crack healing.

[0011] According to a preferred embodiment of the present invention, in step (3), specifically: The clamping and fixing device is opened to separate the two concrete slices. The healing product at the crack is attached to the two concrete slices. Laser ranging is used to scan the two concrete slices to obtain three-dimensional point cloud coordinate data (x, y, z). x and y are the coordinate positions on the polished surface of the concrete slices, and z is the height of the healing product relative to the polished surface. The data is input into MATLAB to construct the three-dimensional undulating surface of the healing product. The three-dimensional undulating surface of the healing product on the two polished surfaces is aligned, that is, the x and y coordinates are aligned. Then, the undulating surfaces of the healing product on the two polished surfaces are stitched together, and the edges of the undulating surfaces are stitched together to realize the reconstruction of the spatial form of the healing at the crack.

[0012] According to a preferred embodiment of the present invention, in step (4), specifically: Based on the reconstructed healing space volume at the crack, it is divided into several parts at equal intervals from the surface to the interior. The volume of the healing product in each part is calculated, and the volume of the crack healing product at different depths is obtained. The total volume of the healing product at the entire crack depth is obtained by summing them up. The ratio of the total volume of the healing product to the original volume of the crack is the crack filling rate. The reconstructed healing space structure at the crack is imported into the fluid analysis finite element software, and a fluid medium is added to obtain the sealing effect after the crack is healed. Using the arithmetic mean height index to evaluate the effective healing width of concrete: S a The arithmetic mean height A This represents the area of ​​the polished surface of the concrete sheet. The healing potential for different crack widths can be assessed with just one test, whereas traditional methods require multiple tests for each crack width. Based on the spatial morphology of the healing products at the reconstructed crack, the crack filling rate, crack healing rate, effective healing width of the crack, and sealing effect after crack healing can be obtained by traditional concrete healing methods. Traditional testing methods require separate testing of the above indicators, while this invention obtains all indicators based on the spatial morphology of the healing products at the reconstructed crack.

[0013] The beneficial effects of this invention are as follows: (1) This invention obtains three-dimensional point cloud data by prefabricating spliced ​​cracks and laser scanning, and uses MATLAB to align and splice the surfaces of the healing products on both sides of the crack, thereby realizing the accurate reconstruction of the spatial form of the healing products and breaking through the limitation of traditional methods that cannot characterize the healing of cracks at different depths.

[0014] (2) This invention utilizes spatial body reconstruction data, which can not only calculate the volume and filling rate of healing products at different depths of cracks, but also import it into finite element analysis tools to further simulate the sealing effect after healing. It can also evaluate the healing potential under different crack widths at once through the arithmetic mean height index, avoiding the complicated process of testing each index separately in the traditional method, and significantly improving efficiency.

[0015] (3) This invention employs an externally added capsule-type healing agent and a superabsorbent polymer in a synergistic design. The crack morphology covers both parallel and V-shaped cracks, and the crack width ranges from 100 to 800 μm. The healing effect is stable, the evaluation range is wide, and the applicability is strong. This testing method can not only be used to evaluate the single healing effect, but also to dynamically track the long-term crack evolution process and study the multiple healing performance, providing a reliable testing basis and technical support for the intelligent and long-life design of concrete. Detailed Implementation

[0016] The present invention will be further illustrated by the following embodiments, but is not limited thereto.

[0017] Example 1: This embodiment provides a method for testing the spatial distribution of concrete crack healing products, applied to parallel cracks. The steps are as follows: Specimen preparation: C40 standard concrete was poured into 100 mm × 100 mm × 100 mm cubes. After curing for 28 days, the cubes were cut into 25 mm thick concrete slices. The slices were polished with 600 to 1500 mesh silicon carbide sandpaper. Anhydrous ethanol was used as the polishing lubricant to ensure that the height difference of the polished surface was within 5 μm. Precast cracks: Two flattened concrete slabs are joined together with a clamping and fixing device, with the flat surfaces facing each other and a parallel gap of 0.4 mm reserved to form a precast crack. The clamping and fixing device is removed after 24 hours of fixation, and the crack remains stable. Healing agent incorporation and curing: Healing capsules with a particle size of 2-6 mm (20% of the aggregate volume in the concrete) and sodium polyacrylate superabsorbent polymer (2% of the cement mass in the concrete) are in situ incorporated into the concrete. Cracked specimens are left to stand for 28 days under 97% relative humidity. The healing capsules consist of, from the inside out: a healing core, a waterproof layer, and an interlocking layer. The healing core comprises the following components by weight: 6 parts calcium sulfoaluminate expanding agent, 1 part silica fume, 3 parts fly ash, 2 parts rice husk ash, and 2 parts waste incineration bottom ash. The calcium sulfoaluminate expanding agent, silica fume, fly ash, rice husk ash, and waste incineration bottom ash are placed in a granulator for granulation, and the surface is sprayed with... The powder is bonded with water or sodium silicate solution, and the resulting particles are dried in an oven at a temperature below 60°C to obtain a healing core. The outer surface of the healing core is coated with polyvinyl alcohol solution or epoxy resin to form a waterproof layer (to prevent premature hydration of the internal material of the core and to provide sufficient chemical substances for subsequent crack healing). The encapsulation is completed, and the outer surface is in contact with standard sand. The sand particles are left on the outer surface of the healing core, and the surface of the healing core is rough and uneven to form an interlocking layer, resulting in an external healing agent. The external healing agent has the characteristics of high solid waste content, particle size not exceeding 8mm, and has the effect of healing cracks. 3D Testing and Analysis: The healed specimen was disassembled, and a laser displacement sensor was used to scan the surface of the crack area of ​​the concrete sheets on both sides to obtain (x,y,z) point cloud data; the data was imported into MATLAB to construct and align the 3D undulating surface to obtain a 3D spatial distribution map of the healing products at the crack. Results evaluation: The healing product was divided into ten depth intervals, and the filling volume of each segment was calculated. The overall filling rate was 82%. The sealing simulation showed that the water flow rate of the crack was reduced by more than 90%, indicating that the healing effect was good.

[0018] Example 2: This embodiment provides a method for testing the spatial distribution of concrete crack healing products. The steps are as described in Embodiment 1, except that the healing core includes the following components in parts by weight: 12 parts calcium sulfoaluminate expansion agent, 5 parts silica fume, 8 parts fly ash, 4 parts rice husk ash, and 6 parts waste incineration bottom ash.

[0019] Example 3: This embodiment provides a method for testing the spatial distribution of healing products in concrete cracks, applied to V-shaped cracks. The steps are as follows: Specimen preparation: Specimens were prepared according to the same concrete mix ratio as in Example 1 and cut into concrete slices with a thickness of 30 mm. After surface polishing, V-shaped cracks with an included angle of 6° (minimum opening 0.15 mm, maximum opening 0.6 mm) were formed using a 3D printed inclined mold and fixed and spliced ​​by a clamp.

[0020] Healing agent design and curing conditions: The healing core was prepared from 10 parts calcium sulfoaluminate expanding agent, 6 parts fly ash, and 3 parts rice husk ash, coated with epoxy resin and adhered with coarse sand to form an interlocking layer, with the particle size controlled at 3-5 mm; the healing capsule dosage was 30% of the aggregate volume, and the superabsorbent polymer was polyacrylic acid-acrylamide copolymer, with a dosage of 3% of the cement mass. The specimens were cured in a dry-wet cycle environment (1h in water / 23h in air, 28d).

[0021] 3D scanning and data processing: After healing, the specimen is disassembled, and a laser ranging system is used to scan the crack area. Point cloud data is reconstructed and stitched together to generate a spatial model of the healing product. The model is then input into finite element software to simulate fluid channel changes.

[0022] Evaluation results: The healing rate at the largest opening of the crack reached 75%, the healing rate in the middle section exceeded 85%, and the overall filling rate reached 79%. Fluid simulation showed that after the V-shaped crack healed, multiple barrier zones were formed inside, and the water flow velocity was significantly reduced, verifying that the present invention can be used for accurate characterization of the spatial healing distribution of complex cracks.

Claims

1. A method for testing the spatial morphological distribution of concrete crack healing products, characterized in that, The steps are as follows: (1) Precast concrete cracks are formed by splicing two concrete pieces together using a clamping and fixing device. (2) Concrete crack healing: design the healing components and the healing environment, and then carry out crack healing; The healing components include an external healing agent and unhydrated cement at the crack. The external healing agent is prepared in the form of a healing capsule. The structure of the external healing agent from the inside out is as follows: healing core, waterproof layer, and interlocking layer. The healing core includes the following components in parts by weight: 6-12 parts calcium sulfoaluminate expansion agent, 1-5 parts silica fume, 3-8 parts fly ash, 2-4 parts rice husk ash, and 2-6 parts bottom ash from waste incineration. Calcium sulfoaluminate expansion agent, silica fume, fly ash, rice husk ash and waste incineration bottom ash are placed in a granulator for granulation. The surface is sprayed with water or the powder is bound with sodium silicate solution. The resulting granules are placed in an oven at a temperature below 60°C to dry, thus obtaining the healing core. The outer surface of the healing core is coated with polyvinyl alcohol solution or epoxy resin to form a waterproof layer, thus completing the encapsulation. The outer surface is then in contact with standard sand, leaving the sand particles on the surface of the healing core. The surface of the healing core becomes rough and uneven, forming an interlocking layer, thus obtaining an external healing agent. By utilizing unhydrated cement at the cracks and adding superabsorbent polymers to the concrete, efficient healing of different crack shapes and widths can be achieved, combining external replenishment and internal generation of healing products. (3) Test on the spatial distribution of healing at concrete cracks: Two concrete slices were separated, and the healing products at the cracks were attached to the two concrete slices. The spatial distribution of the healing products at the cracks was reconstructed. The clamping and fixing device is opened to separate the two concrete slices. The healing product at the crack is attached to the two concrete slices. Laser ranging is used to scan the two concrete slices to obtain three-dimensional point cloud coordinate data (x, y, z). x and y are the coordinate positions on the polished surface of the concrete slices, and z is the height of the healing product relative to the polished surface. The data is input into MATLAB to construct the three-dimensional undulating surface of the healing product. The three-dimensional undulating surfaces of the healing product on the two polished surfaces are aligned, that is, the x and y coordinates are aligned. Then the undulating surfaces of the healing product on the two polished surfaces are spliced ​​together, and the edges of the undulating surfaces are spliced ​​together to realize the reconstruction of the spatial form of the healing at the crack. (4) Evaluation of the healing potential of concrete cracks: Based on the healing space morphology at the reconstructed crack, the crack filling rate, the effective healing width of the crack, and the sealing effect after crack healing are obtained. Based on the reconstructed healing space volume at the crack, it is divided into several parts at equal intervals from the surface to the interior. The volume of the healing product in each part is calculated, and the volume of the crack healing product at different depths is obtained. The total volume of the healing product at the entire crack depth is obtained by summing the volumes. The ratio of the total volume of the healing product to the original volume of the crack is the crack filling rate.

2. The method for testing the spatial morphological distribution of concrete crack healing products as described in claim 1, characterized in that, In step (1), a concrete cube is prepared, and the concrete cube is cut into slices with a thickness of 15mm-35mm. The concrete slices are then polished, and the exposed surface is used as the polishing surface. Two concrete slabs are joined together using a clamping and fixing device, with the polished surfaces facing each other and a joint reserved. The joint is a precast crack in the concrete, which can be a parallel crack or a V-shaped crack.

3. The method for testing the spatial morphological distribution of concrete crack healing products as described in claim 2, characterized in that, In step (1), the spacing between parallel cracks is 100-800 μm, and the opening angle of the V-shaped cracks is 3°-10°.

4. The method for testing the spatial morphological distribution of concrete crack healing products as described in claim 3, characterized in that, In step (1), 600-mesh, 800-mesh, 1200-mesh, or 1500-mesh diamond or silicon carbide sandpaper is used for polishing. Anhydrous ethanol or isopropanol is used as the polishing lubricant. The height difference of the polished surface is between 100 nm and 20 μm.

5. The method for testing the spatial morphological distribution of concrete crack healing products as described in claim 4, characterized in that, The dosage of healing capsules is 5%-50% of the aggregate volume in concrete, and the dosage of superabsorbent polymer is 0.5%-5% of the cement mass in concrete, with the ratio of the two dosages maintained at 10:

1.

6. The method for testing the spatial morphological distribution of concrete crack healing products as described in claim 5, characterized in that, In step (2), the healing environment is a 97% relative humidity environment and a wet-dry cycle in water for 28 days to achieve the healing of concrete cracks; The superabsorbent polymer is sodium polyacrylate or polyacrylic acid-acrylamide copolymer, with a balanced swelling rate not exceeding 289 g / g.

7. The method for testing the spatial distribution of concrete crack healing products as described in claim 6, characterized in that, In step (4), the reconstructed healing space structure at the crack is imported into the fluid analysis finite element software, and a fluid medium is added to obtain the sealing effect after the crack is healed. Using the arithmetic mean height index to evaluate the effective healing width of concrete: ; S a The arithmetic mean height A This represents the area of ​​the polished surface of the concrete sheet.

Citation Information

Patent Citations

  • Method used for representing cement based material surface crack self-healing effect based on healed product volume

    CN108344860A

  • Method for measuring expansion rate of single-particle SAPs in cracks

    CN110411829A

  • Capsule-matrix self-healing material with high compatibility and preparation method thereof

    CN120535229A